A fatal case of Vibrio cholerae-associated diarrhea and bacteremia in a 30-year-old carrier of beta-thalassemia. - Islam, Mohammad Tarequl.; Nahar, Kazi Sumaita.; Ara, Nikhat.; Biswas, Suma Mita.; Waliullah; Tasnim, Jarin.; Sakib, Mohammad Nazmus.; Al-Mamun, Abdullah.; Islam, Alimul.; Bristi, Anindita.; Sultana, Marzia.; Ahmed, Dilruba.; Seed, Kimberley D; Camilli, Andrew.; Ahmed, Tahmeed.; Alam, Munirul. (Tufts University. Tisch Library., 2025)
Springer Open.